2021
DOI: 10.3390/polym13020282
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Degradation in Composting Environment of Active Polylactic Acid Bilayer Nanocomposites Films: Combined Role of Umbelliferone, Lignin and Cellulose Nanostructures

Abstract: This study was dedicated to the functional characterization of innovative poly(lactic acid) (PLA)-based bilayer films containing lignocellulosic nanostructures (cellulose nanocrystals (CNCs) or lignin nanoparticles (LNPs)) and umbelliferone (UMB) as active ingredients (AIs), prepared to be used as active food packaging. Materials proved to have active properties associated with the antioxidant action of UMB and LNPs, as the combination of both ingredients in the bilayer formulations produced a positive synergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
3
0
1
Order By: Relevance
“…Thus, the addition of both the organic and inorganic NPs speeds up the disintegration phenomenon. During composting, the material disintegration process begins with a hydrolysis process; the hydrolytic degradation of PLA starts with water absorption followed by the breaking of the polymer chain via ester bonds in the amorphous phase [ 18 , 59 ], which is further attacked by the enzymes of microorganisms at the initial stage of this process. It should be highlighted that the electrospun PLA-based nanocomposites exhibited reduced crystallinity, with the exception of the PLA/CNC and PLA/CNC- g -PLLA electrospun nanocomposites (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the addition of both the organic and inorganic NPs speeds up the disintegration phenomenon. During composting, the material disintegration process begins with a hydrolysis process; the hydrolytic degradation of PLA starts with water absorption followed by the breaking of the polymer chain via ester bonds in the amorphous phase [ 18 , 59 ], which is further attacked by the enzymes of microorganisms at the initial stage of this process. It should be highlighted that the electrospun PLA-based nanocomposites exhibited reduced crystallinity, with the exception of the PLA/CNC and PLA/CNC- g -PLLA electrospun nanocomposites (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…PLA presented a WCA value of 67.2 • , similar to that obtained by Carbonell-Verdú et al [22], while PBAT showed a significantly higher WCA value of 74.1 • , being more hydrophobic. The PLA/PBAT blend showed even significantly higher values than those of PBAT, probably due to the high roughness of this formulation since the wettability is strongly dependent not only on the surface chemical properties but also on the surface topography [55]. The incorporation of GR into the PLA/PBAT blend produced a significant decrease (p < 0.05) of the WCA, particularly evident in those formulations with a high amount of GR (15 and 20 phr), increasing the hydrophilicity of the surface.…”
Section: Wettability Performance Of Filmsmentioning
confidence: 94%
“…This advancement aligns with the global shift towards eco-friendly materials and the reduction in plastic waste. PLA/Lignin films offer a scientifically supported, environmentally responsible alternative that holds great promise for a more sustainable and greener future in the packaging industry [33,34].…”
Section: Introductionmentioning
confidence: 99%